Dynamic solidification model of low-density FeCrNiAl multi-component alloy. (February 2021) - Qiao, Ling; Zhu, Jingchuan; Teng, Yu; Bao, Aorigele; Lai, Zhonghong; Wang, Yuan
Abstract: The present study proposes a dynamic model to describe the solidification characteristics of FeCrNiAl multi-component alloy. The as-cast FeCrNiAl multi-component alloy was prepared via vacuum arc melting technique and its crystal structure, microstructure, density and hardness were reported. The alloy has the density of 6.72 g/cm3 and hardness value of 491 kgf/mm, respectively. The FeCrNiAl alloy is a double-phase alloy consisting of the ordered (Ni, Al) phase and disordered [Fe, Cr] phase. The morphology of alloy was dendritic structure with the segregation of Al and Ni elements in dendritic regions as well as the Cr and Fe in interdendritic regions. The experimental data combined with the results of the thermodynamic modeling reveals that the (Ni, Al) phase firstly solidified from the melt as the primary phase. While the [Fe, Cr] phase distributes in the interdendritic region. At the end of solidification, the two bcc phases coexist, which indicates the formation of (Ni, Al)/[Fe, Cr] eutectics. Moreover, the thermodynamic parameters Ω and δr confirms the stability of solid solution phases in FeCrNiAl multi-component alloy. And the simplified dynamic solidification model proposed in this paper would provide theoretical explanation for the formation of its double-phase structures. Graphical abstract: Image 1 Highlights: FeCrNiAl high-entropy-alloy was prepared by the vacuum arc melting technique. The morphology of alloy was dendritic-structure. [Ni, Al] phase affiliates with the primary dendrite phase and interdendritic region is [Fe, Cr] rich. The formation mechanism of double-phase was discussed.